Нечіткі моделі в задачах підбору персоналу при формуванні соціальных груп - Kondratenko, N. R.; Luzhetskyi, S. V.; Cheboraka, O. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
Fuzzy models in staff recruitment problems during the social groups forming are considered. The fuzzy model which is used by information system — adviser that helps expert to recruit and evaluate staff, is proposed.